The Effect of Substitution of LDPE Plastic, Coconut Fiber, and Seashell as Mixed Raw Materials for Paving Blocks - Ratnawati, Kania; Nisah, Firda Ainun; Azizie, Yona Tasya (Jurnal Pijar Mipa, 2024)
Human life is inseparable from the use of plastic in everyday life. LDPE plastic significantly impacts the environment as it is difficult to decompose naturally. On the other hand, natural waste such as seashells and coconut fiber are often found without further processing needs to recycle. To overcome this issue, there must be an effort to recycle these wastes. This research aims to determine the substitution effects of recycled products (LDPE plastic, seashells, coconut fiber) in producing paving blocks. The paving block is made with 2 main variations: a mixture of LDPE plastic and seashells (X1 and X2) and a mixture of LDPE plastic and coconut fiber (Y1 and Y2). The results show that paving block X has a higher compressive strength than paving block Y. The best paving block mixture is variation X2, which has a maximum load of 11 kN, a compressive strength of 46.797 kgf/cm2, and a maximum water absorption capacity of 4,8 %. The compressive strength values from the variations of the produced paving blocks are below the quality requirements set by SNI03-060292-1996. However, producing paving blocks with LDPE plastic, seashells, and coconut fiber can positively address waste issues in the Karawang Regency community through recycling practices.